2013 Proceedings IEEE INFOCOM 2013
DOI: 10.1109/infcom.2013.6567140
|View full text |Cite
|
Sign up to set email alerts
|

Economic models of sponsored content in wireless networks with uncertain demand

Abstract: Due to copyright restrictions, the access to the full text of this article is only available via subscription.The interaction of a content provider with end users on an infrastructure platform built and maintained by a service provider can be viewed as a two-sided market. Content sponsoring, i.e., charging the content provider instead of viewers for resources consumed in viewing the content, can benefit all parties involved. Without being charged directly or having it counted against their monthly data quotas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…where dS m (p) dp = −m(p) by the definitions of S m (p) and m(p) in Equation (7) and (2). Similarly, the impact of the CP-side price q on social welfare W is ∂W (p, q, µ) ∂q…”
Section: B Proofs Of Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where dS m (p) dp = −m(p) by the definitions of S m (p) and m(p) in Equation (7) and (2). Similarly, the impact of the CP-side price q on social welfare W is ∂W (p, q, µ) ∂q…”
Section: B Proofs Of Theoretical Resultsmentioning
confidence: 99%
“…Since the sponsorship offers a way for CPs to subsidize their users and indirectly transfer value to APs, it could be seen as a variant of the two-sided pricing model. Some work [2,14,29] have studied this variant and showed that it benefits both CPs and APs. Because APs charge users different prices for content traffic from different CPs, the sponsored data plan is also considered as a type of price discrimination in disguise and has raised concerns from the FCC who says that they will be monitoring and prepared to intervene if necessary [18].…”
Section: Related Workmentioning
confidence: 99%
“…Other papers [5], [12], [13] study sponsored content in relation to different notions of net neutrality. Paper [1] focused on an off-line setting where the content provider has to decide in advance how much content it is willing to sponsor during an upcoming month. Accesses to the content are charged against this amount until it is depleted at which point end users have to revert to paying for access.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work (e.g. [1]) has analyzed sponsored content in an offline setting where sponsoring decisions are made before requests for traffic arrive. The goal of this paper is to propose a model for how sponsored content could work in an online setting where sponsoring decisions are made in real-time as traffic requests arrive.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are currently few academic works directly related to this new pricing strategy. From the economic point of view, Andrews et al [13] studied the contractual relationship between the service providers and content providers. They modeled the interaction between the service providers and the content providers as a Stackelberg game with random demand.…”
Section: Related Workmentioning
confidence: 99%